2016
DOI: 10.1186/s12876-016-0506-4
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of pegylated interferon plus ribavirin for treatment of chronic hepatitis C in Thailand: genotype 1 and 6

Abstract: BackgroundPegylated interferon alpha 2a, alpha 2b and ribavirin have been included to the National List of Essential Medicines (NLEM) for treatment of only chronic hepatitis C genotypes 2 and 3 in Thailand. This reimbursement policy has not covered for other genotypes of hepatitis C virus infection (HCV) especially for genotypes 1 and 6 that account for 30-50 % of all HCV infection in Thailand. Therefore, this research determined whether pegylated interferon alpha 2a or alpha 2b plus ribavirin is more cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Studies in neighboring countries have reported the cost of Peg-IFN using the same doses. One study from Thailand reported that the Peg IFN-2a/2b and ribavirin for treating HCV genotypes 1/6 cost US$90 per week (2013 prices) 30 , which is similar to our finding. Another study reported that in China 31 , the Peg IFN-2a and ribavirin for treating HCV genotype 1, cost US$174 per week (2016 prices), almost double our estimate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies in neighboring countries have reported the cost of Peg-IFN using the same doses. One study from Thailand reported that the Peg IFN-2a/2b and ribavirin for treating HCV genotypes 1/6 cost US$90 per week (2013 prices) 30 , which is similar to our finding. Another study reported that in China 31 , the Peg IFN-2a and ribavirin for treating HCV genotype 1, cost US$174 per week (2016 prices), almost double our estimate.…”
Section: Discussionsupporting
confidence: 90%
“…Whilst it is possible that there may be some minor variations in costs in other provinces in Vietnam, as the costs of both healthcare services and drugs are regulated centrally by the NHI department and MoH, our cost estimates are likely to be robust. Although the precise results and cost estimates of our study are not directly generalizable to other countries, they are consistent with reports from neighbouring countries, such as Thailand 30 . It is important that further HCV treatment costing studies are conducted in other low- and middle-income countries, particularly relating to the use of DAAs.…”
Section: Discussionsupporting
confidence: 82%
“…Health outcomes were expressed in terms of quality adjusted life years (QALYs). The structure of the model was based from the previous model of hepatitis C treatment recommendation in Thailand [ 8 ] which was modified to include anemia–the most common adverse event in treating chronic hepatitis C.…”
Section: Methodsmentioning
confidence: 99%
“…Transitional probabilities between health states were obtained from previously published economic evaluation [ 8 ]. To acquire probabilities of treatment-associated anemia, data from previous studies were reviewed through meta-analysis using STATA version 14.…”
Section: Methodsmentioning
confidence: 99%
“…A hybrid of decision-tree and Markov models adapted from Kapol et al 23 was applied, which was validated by clinical experts in Vietnam’s National Hospital of Tropical Diseases.…”
Section: Methodsmentioning
confidence: 99%